ANALISIS KESULITAN METAKOGNISI SISWA DALAM MEMECAHKAN MASALAH SISTEM PERTIDAKSAMAAN LINEAR DUA VARIABEL DITINJAU DARI TIPE KEPRIBADIAN GUARDIAN, ARTISAN, RATIONAL, DAN IDEALIST KELAS X SMKN I JOMBANG - Fitria, Camelina; Sujadi, Imam; Subanti, Sri (Jurnal Pembelajaran Matematika, 2016)
Abstract: The aim of this research was to know metacognition and the difficulty of studentâs metacognition in solving problem of linear inequality system with two variables at Xth grades of SMKN I Jombang based on personality type guardian, artisan, rational, and idealist. The type of this research was a qualitative research on case study. Subjectâs selection procedure was by using purposive sampling. There were 9 subjects in this research including 3 guardian type, 2 artisan type, 2 rational type, and 2 idealist type. Data collection technique was task-based interviews. The validity was determined by time triangulation. The data analysis technique in this research was reduction, data display, and conclusion. The data was analyzed based on metacognition indicator. Subject experienced metacognition difficulty if he could not fulfill metacognition indicator. The results of this research showed that guardian and rational students did not experience any metacognition difficulty. Artisan and idealist students experienced metacognition difficulties in knowledge strategy aspect, those were difficult in using the concept despite knowing the purpose of the question, did not re-read the part that were not understood, sure that did not find any fault in solving problem when the steps used was not appropriate, and did not fix the error although confused on step solution. In aspect of task cognitive knowledge, artisan and idealist type did not know the algorithm used and did not know the step to resolve the problem. In self knowledge aspect, idealist type was not aware if finding difficulty in determining the measures to solve the problem and did not realize the completion of the steps used were wrong, but the students stayed on confidence on their solving problem.Key words: Metacognition Difficulty, Problem Solving, Personality Type